Commanding a police operation with a Mobile Distribution Point of ICT Infrastructure .......... 43 - Kasprowicz, Grzegorz; M. Zabołotny, Wojciech; Poźniak, Krzysztof; Tyburska, Agata; Struniawski, Jarosław (Systemy bezpieczeństwa: Wymiar lokalny i państwowy, 2020)
Currently public safety is threatened by emergencies related to broadly understood terrorism, natural disasters and technical failures or are related to mass events, public gatherings and state or religious ceremonies and other situations causing risks involving a potential loss of control over the course of events. Hence, the Police must take specific actions carried out as part of organized police activities, primarily police actions and operations. The efficiency and effectiveness of the command in the Police is dependent on developing new, alternative, innovative technical solutions. The Mobile Distribution Point of ICT Infrastructure (Pol. MPDIT) serves as an example in this respect. It will be an autonomous node that integrates technologically advanced ICT services, such as voice, data, and image transmission and GPS positioning, for the needs of mobile command posts and the provision of ICT infrastructure in a specific area. This type of device is currently unavailable to the Polish Police, which limits the effectiveness of its operation in emergencies.